Probe Signal Values in mRNA Arrays Imply an Excessive Involvement of Neutrophil FCGR1 in Tuberculosis - Wu, Kang; Li, Meng; Chen, Zhen-yan; Lowrie, Douglas B.; Fan, Xiao-Yong (Frontiers in Medicine, 2020)
The perturbed genes from transcriptomes are often presented in terms of relative expressions against control samples. However, the probe signal values (PSVs) of genes, implying protein abundances, are often ignored. Here we explored the PSVs in tuberculosis (TB)-relevant signature genes. The signatures from Mycobacterium tuberculosis-infected THP-1 cells were defined as induced (TMtb-i, with a derived TMtb-iNet) and repressed (TMtb-r). The signature from human blood was defined as a pulmonary TB (PTB)-specific signature (PTBsig). The analysis showed that before infection, TMtb-i and TMtb-iNet had lower PSVs and TMtb-r genes had average PSVs. In the blood of healthy donors, PTBsig (divided into up-regulated PTBsigUp and down-regulated PTBsigDn) displayed average PSVs. This was partly due to masking by the cellular heterogeneity of blood; diverse PSVs were seen in constituent cell populations (CD4/8+ T, monocytes and neutrophils). Specifically, the PSVs of PTBsigUp in the neutrophils of healthy donors were higher (implying higher protein abundances), and much higher in the neutrophils of PTB (implying excessive protein abundances). Based on the PSVs patterns of PTBsigUp in four cell populations, we identified three representative highly homologous genes (FCGR1A, FCGR1B and the pseudogene FCGR1CP, which were often poorly distinguished), of which the summed PSVs were the highest in the neutrophils of PTB patients and healthy donors. The three genes were all up-regulated and responsive to chemotherapy in the blood of PTB, as validated in a RNA-seq-based analysis. This PSV-based study confirms the excessive involvement of neutrophil FCGR1 in PTB.